Thomas Aquinas on the Classification of Virtues - Ahmad Reza Meftah (اخلاق وحیانی, 2014)
The Classification of virtues is difficult. The similarities and differences between virtues has made various lists of virtues. Thomas Aquinas, the Catholic Church theologian who has rational concerns about the Christian religion, has offered the lengthiest classification of virtues in his book "Summa Theologica". He has divided virtues in two  philosophical and theological approach. His philosophical approach about virtues is based on Aristotle's philosophical views and his theological approach is based on New Testament. In the philosophical division, He has divided virtues in two categories; intellectual virtues and moral virtues. intellectual virtues are the virtues that rooted in the man's rational nature and moral virtues are the virtues that refer to human behavior. Aquinas develops this division based on  dividing reason into theoretical and practical reason, and also based on the issue that wethere virtues are types of active or passive. But in the theological approach to the division of virtues he divides them in two categories; cardinal virtues and theological virtues.Theological virtues, namely faith, hope and love, are those virtues that refer to man's relationship with God. Cardinal virtues, namely prudence,temperance, fortitude, justice are virtues that are acquired. Thomas Aquinas states the basis of  divisions and branches of any of these virtues in detail that we will discuss about in this article.